PRELIMINARY DESIGN FOR THE PRODUCTION SYSTEM OF RED SPINACH AND GREEN SPINACH USING ORGANIC FERTILIZERS WITH A COMMUNITY SUPPORTED AGRICULTURE (CSA) DISTRIBUTION MODEL IN URBAN AREAS - Tiara Paraditha, Adzkia
Food security is a fundamental need that is an important indicator of a country's stability. The higher the food demand, the lower the food security. In Indonesia, one of the main challenges in the food sector is meeting the demand for nutritious vegetables such as spinach. Spinach is rich in essential nutrients, including iron, folate, and antioxidants essential for human health. The demand for spinach continues to increase as people become more aware of healthy eating habits and the importance of consuming vegetables to prevent various diseases. Spinach also has a high antioxidant content, especially vitamin C. Green spinach contains 160 mg of vitamin C per 100 grams, while red spinach contains 370 mg per 100 grams. Consuming only 20-50 grams of spinach can meet the daily vitamin C requirement of 75-90 mg. Therefore, the production of high-quality and sustainable spinach is very important. The increasing interest in nutritious vegetables such as spinach emphasizes the importance of agricultural strategies that can produce high-quality spinach sustainably. Environmental degradation from synthetic fertilizers is a major challenge in modern agriculture. Synthetic fertilizers, although they can increase plant growth in the short term, have negative long-term effects. These fertilizers decrease soil quality, both physically, chemically, and biologically, and reduce the content of organic matter and microbes essential for soil fertility. In Indonesia, around 14 million hectares of land have experienced soil degradation by 2018. On the other hand, environmental pollution due to organic waste is a global issue. Organic waste production in Indonesia can reach 28.35 million tons per year. To overcome these problems, organic farming is beginning to be seen as a sustainable solution. Therefore, effective organic farming strategies are needed to address these problems, including the addition of liquid organic biofertilizer (LOB) and vermicompost to enrich microorganisms and organic matter in the soil. In addition, making vermicompost can also be a solution to reduce the amount of organic waste that continues to increase every year. To support the implementation of these organic farming strategies, collaborative models such as Community Supported Agriculture (CSA) can be used as a momentum for the attention of modern society today in supporting local agricultural production. The CSA model allows consumers and producers to share risks and profits in cultivation but also involves collaboration within the community to achieve common goals. With the CSA model, consumers can obtain fresh vegetables grown with organic fertilizers on a regular basis and alternatives for household waste management. Therefore, this research aims to design and conduct a financial feasibility study for the red and green spinach production system using organic fertilizers with the Community Supported Agriculture (CSA) distribution model in urban areas. This preliminary design is expected to improve agricultural sustainability and reduce the negative impact of organic waste on the environment. The pre-design utilizes a 358.8 m² plot, with 165.6 m² dedicated to cultivation. The cultivation plan includes 10 rows of red spinach and 10 rows of green spinach, each row consisting of 52 polybags. The cultivation process involves preparing the planting medium with soil and vermicompost (3:1) for red spinach and soil and compost (2:1) for green spinach. Seeds are sown at a rate of 30 seeds/polybag, with thinning done at 10 DAS (days after sowing) to leave 9 plants. Watering is performed in the morning and evening with a volume of 230 ml/polybag/day. For green spinach, LOB is added at 150 ml/polybag per application, starting from 10 DAS and applied weekly. Hill management is conducted at 14 DAS to maintain the root area. Pest and disease management involves applying biopesticides at 20 DAS. Harvesting is done at 30 DAS. The pre-design comprises two alternatives: the first involves commercial cultivation of green spinach with compost and LOB, and red spinach with vermicompost. The second involves commercial cultivation of green spinach with compost and LOB, and self-sustained cultivation of red spinach with vermicompost. Economic analysis shows that the first alternative has an R/C ratio of 1.47, while the second has an R/C ratio of 1.93. Thus, the second alternative is chosen for this pre-design. The integrated system is projected to produce 2,821.35 kg per cycle of green spinach, 1,178.95 kg per cycle of red spinach, 3,420 packs per cycle of spinach juice, 12,304 kg per cycle of vermicompost, and 1,123 kg per cycle of earthworm hatchlings. In the first year, cultivation will occur over nine planting periods with 520 polybags per period per commodity. Each commodity is graded A, B, or C, with 15% of grade C green spinach processed into juice in 8 batches per cycle. Vermicompost sales begin in the third month post-processing, yielding 256 kg weekly. Earthworm hatchlings are produced in 10 batches of 112 kg each. The pre-design will be implemented on vacant land in Jatinangor City Park, Cibeusi, Jatinangor, West Java, at coordinates 06°56'26.70"S, 107°45'48.59"E, at 692 meters above sea level. The total area is 358.8 m², including greenhouse (11.5 × 14.4 m²), vermicomposting building (6 × 3 m²), vermicompost storage (6 × 3 m²), drying area (6 × 4 m²), drum storage (3 × 1.4 m²), chopping area (3 × 1.4 m²), packing house (3 × 3 m²), office (3 × 3 m²), and vehicle parking (17.5 × 2 m²). The pre-design cultivation system consists of 4 subsystems: red spinach cultivation, green spinach cultivation, vermicompost production, and spinach juice production. The red spinach subsystem has a total mass balance of 40,312.75 kg/cycle and an energy balance of 64,297.31 MJ/cycle. The green spinach subsystem has a total mass balance of 43,269.86 kg/cycle and an energy balance of 64,318.95 MJ/cycle. The vermicompost production subsystem is divided into preparation and bioconversion units. The organic waste preparation unit has a total mass balance of 20,116.95 kg/cycle and an energy balance of 749.84 MJ/cycle, while the bioconversion unit has a total mass balance of 23,242.88 kg/cycle and an energy balance of 408.54 MJ/cycle. Meanwhile, the spinach juice production subsystem has a total mass balance of 611.88 kg/cycle and an energy balance of 80.23 MJ/cycle. Based on mass balance calculations, it is found that to produce each product in the amount of 1 kg, the required input and resulting by-products are as follows: a.Red spinach biomass (1 kg): Input: soil (1.4 kg), vermicompost (0.6 kg), redspinach seeds (0.06 grams), air (0.02 kg), water (32.13 kg), biopesticides (0.02kg). By-products: spinach residues (0.13 kg), air (0.02 kg), residual water fromevaporation and percolation (31.15 kg), final growing medium (1.89 kg), and loss(0.002 kg). b.Green spinach biomass (1 kg): Input: soil (0.45 kg), compost (0.37 kg), redspinach seeds (0.02 grams), LOB (0.03 kg), air (0.02 kg), water (12.16 kg),biopesticides (0.01 kg). By-products: spinach residues (0.13 kg), air (0.02 kg),residual water from evaporation and percolation (11.06 kg), final growing medium(0.82 kg), and loss (0.0002 kg). c.Vermicompost (1 kg): Input: prepared waste (1.47 kg), air (0.41 kg), worms (0.047kg). By-products: young worms (0.09 kg), air (0.23 kg), and loss (0.57 kg). d.Spinach juice (1 kg): Input: green spinach (0.94 kg), pineapple (0.11 kg), water(0.09 kg), honey (0.01 kg). By-products: spinach juice pulp (0.16 kg). Based on economic analysis, the initial investment cost is Rp259,623,945.00, covering the spinach cultivation unit, vermicompost and worm seedling production unit, spinach juice production unit, office unit, and transportation unit. The investment cost in the first year is Rp259,623,945.00, while in the second, fourth, and fifth years, it is Rp0.00, and in the third year, it is Rp904,040.00. The cost to produce 1 kg of red spinach is Rp14,314; green spinach is Rp2,877; vermicompost is Rp961; and worm seedlings are Rp3,204. The cost to produce one bottle of spinach juice is Rp17.21. Thus, the total production cost for this preliminary design in one cycle is Rp129,197,243.62 in the first year and Rp141,026,704.73 in subsequent years. The sales estimate for the first year is Rp293,384,472.50, and from the second to the fifth year, it is Rp382,973,696.67 per year. The break even point (BEP) for each product is as follows: red spinach Rp139.982.250, green spinach Rp130.038.632, spinach juice Rp8.567.560, vermicompost Rp52.451.167, and worm seedlings Rp45.652.353. The profit and loss report indicates the Net Cash Inflow - Outflow as follows: year 0 at -Rp259,623,945, year 1 at Rp164,187,229, year 2 at Rp221,088,591.93, year 3 at Rp220,184,552, year 4 at Rp221,088,591.93, and year 5 at Rp221,088,592. This venture is economically viable with a Net Present Value (NPV) of Rp525,843,548.06, a Benefit-Cost (B/C) ratio of 3.025, an Internal Rate of Return (IRR) of 70%, and a payback period of 2 years, 9 months, and 3 days.